2020
DOI: 10.38124/ijisrt20jun081
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Undiagnosed Hypertension among the Hypertensives Living in the City of Boma. Republic Democratic Republic of the Congo

Abstract: Undiagnosed and uncontrolled hypertension are responsible for several cardiovascular complications, particularly in countries with limited resources. The objective of this study was to assess the extent of undiagnosed hypertension in the adult hypertensive in Boma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Older age was associated with hypertension in the present study. Our observation is in agreement with the results of previous studies carried out in the DRC which found that advanced age as one of the main determinants of hypertension in Congolese environment [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Older age was associated with hypertension in the present study. Our observation is in agreement with the results of previous studies carried out in the DRC which found that advanced age as one of the main determinants of hypertension in Congolese environment [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
“…In the Democratic Republic of Congo (DRC), hypertension, considered rare or even non-existent in the general population in 1960 [10], has currently reached a prevalence of around 40% in both urban and rural areas [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In the Democratic Republic of the Congo (DRC), then nationwide prevalence of hypertension, in studies conducted in some urban and rural areas have reported a prevalence of hypertension ranging from 30% to 40% [9,[12][13][14][15][16].…”
Section: Introdutionmentioning
confidence: 99%